Composition chimique et évaluation du potentiel anti oxydant d’Inula viscosa L. - ADOUL, NEBIA LINA; BOURAS, AMINA (My University, 2025)
The active constituents of medicinal plants represent new opportunities for the development and creation of new medicines. Inulaviscosa L belongs to the Asteraceae family and is commonly found in the Mediterranean basin. In traditionnelmédicine, Inula viscosa L. (Asteraceae) leaves are frequently used to treat abscesses, infections, abdominal pain and headaches, hemorrhoids, diabetes, digestive disorders, as well as to heal open wounds, stop bleeding and promote skin healing. The aim of this research was to determine the polyphenol, flavonoid and tannin content of Inulaviscosa L. leaves, and to evaluate the antioxidant capacity of three different extracts: methanolic, ethanolic and hexanolic, from this plant grown at Sidi Ali in the wilaya of Mostaganem in western Algeria. For each Inulaviscosa L. extract examined, antioxidant capacities were estimated by DPPH (2,2 diphenyl-1-picrylhydrazyl) trapping and the chemical composition of each extract was determined.the results obtained show that the extracts analyzed contain significant phenolic compounds, tannins and flavonoids, as well as a very fable antioxidant potential. The results of the quantitative evaluation show the presence of polyphenols with a content varying between (28.766 and 63.103 mg/EAG), and hydrolysable tannins with a content varying between (19.943 and 35.137mg/EAT), as well as flavonoids with a quantity varying between (17.337 and 22.176 mg/EQ). Evaluation of the antioxidant potential of these three extracts shows that the IC50s of the plant extracts evaluated were (179.043 21.395) for the methanolic extract, (162.367 3.460) for the ethanolic extract and (40.653 0.548) for the hexanolic extract, respectively, compared with those of ascorbic acid (IC50 of (0.670 0.012), thus minimizing its antioxidant activity.
Keywords: Inula viscosa .L, polyphenols, hydrolyzable tannins, flavonoids, and antioxidant activity